Modified Russell network model for determining Malaysia water supply services performance - Wan Rosmanira Ismail,; Norbaizura Kamarudin, (Penerbit Universiti Kebangsaan Malaysia, 2020)
A black-box analysis of Data Envelopment Analysis (DEA) has been widely used to measure water supply services performance. It is a single process, which does not take into account the internal structure of the operation. However, in the production of water supply services, rather than a black-box analysis, the operation can be expressed into a two-stage network process and therefore can be analysed using Network Data Envelopment Analysis (NDEA). Furthermore, the Network Russell (NR) model is one of many other models in NDEA. A modified NR model is introduced in this study, which incorporated an undesirable output factor and will be called Network Russell with Undesirable Output (NR-OU) model. The NROU model has been tested on data of water supply from 14 states in Malaysia and the results provide information about the stages or processes in the operation that needs more attention in order to improve the Malaysian water supply services performance.